Violência ocupacional contra profissionais de saúde em um hospital de urgência. natal/rn, 2009 - Morais Filho, Luiz Alves (2009)
Descriptive exploratory study, with quantitative approach, with data collected from April to May 2009, aiming to identify the types of occupational violence affecting professionals on the nursing and medical staff in an emergency hospital service in Natal/RN, over the last 12 months; to identify emergency sectors where occupational violence episodes took place; to characterize aggressors on each type of occupational violence; to know the procedures adopted after each violent act targeting nursing and medical staff professionals; and to know the consequences of violence suffered by the nursing and medical staff professionals. The sample consisted of 26 nurses, 95 nursing assistants/technicians and 124 physicians, for a total of 245 professionals. The results showed that 50.61% of the professionals were women, aged 41 to 45 (22.45%), with post-graduate studies (51.43%), married (60.82%); 21.22% had 16 to 20 years of experience in the profession and in emergency practice; working 40 weekly hours (86.12%); and working both the day shift and the night shift (70.21%); 27.35% consider violence to be a part of their profession and the patient s companions as an important risk factor (86.53%); couldn t inform whether there was a specific established procedure for reporting occupational violence (45.71%); 73.06% suffered occupational violence in the 12 months; 70.20% verbal assault, 24.08% moral harassment, 6.12% physical assault, and 3.67% sexual harassment; 66.67% of the patients took part in the physical assault; the companions, in verbal assault (58.14%); and the health staff in moral harassment (69.49%); facing episodes violence, 37.65% of the professionals reported the fact to their co-workers; 57.25% uffered from stress as a consequence; on 4.71% of the episodes the professionals had to be bsent from work, resulting in 75 days of occupational violence-related absence. We conclude here was a high rate of occupational violence in the researched population, with verbal ssault and moral harassment as the most frequent violence types. Because factors related to ccupational violence were very diverse, actions seeking to confront this problem shouldn t be limited to the work environment itself. Education ought to be one of the most effective ctions for avoiding or minimizing these events occurrence